The Examination on Mobile Banking’s Use Behavior of Retired Chinese in Shaoxing - Wu, Xia (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
This study aims to determine the factors that affect how retired Chinese customers use mobile banking. The conceptual framework focuses on the relationship between perceived usefulness, trust, pricing value, user satisfaction, behavioral intention and use behavior of mobile banking applications. The researcher employed quantitative method to distribute questionnaires to 450 retired Chinese in Shaoxing, who have been using the Agricultural Bank of China (ABC), China Construction Bank (CCB), and Industrial and Commercial Bank of China (ICBC)’s mobile banking applications. The nonprobability sample includes judgmental, quota, convenience sampling. Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM) were used for data analysis, including model fit analysis, reliability and construct validity. The results show that perceived usefulness, pricing value, trust, and user satisfaction have significant impacts on behavioral intention, and perceived usefulness has a significant impact on user satisfaction, while behavioral intention has a significant impact on user behavior. Six hypotheses were accepted to fulfill research objectives. Therefore, mobile banking application development needs to pay more attention to the perceived usefulness, pricing value, trust, behavioral intention, and user satisfaction aspects of the research and development efforts.